Determinants of student satisfaction in higher education: an empirical study in Dubai. (11th December 2012) - Parahoo, Sanjai K.; Tamim, Rana M.
We develop and empirically validate a student satisfaction modelling technology-enabled university environments. We use focus groups at a university in Dubai and an intensive literature review to propose a theoretical model that involves different types of student interactions; perceptions of infrastructure; and university branding as independent variables influencing student satisfaction as outcome variable. Using data collected from a random sample of 99 students, we empirically test the model using linear regression analysis. Two variables, branding and interactions of students with administrative staff are found to significantly influence student satisfaction, accounting for 61% of variance. Implications are discussed and suggestions for future research are given. With its specific context, the study requires replication in other countries to determine whether the findings are generalisable. This study is one of the rare occasions when a structural model of student satisfaction in technology-enabled environments in the Middle East has been subjected to empirical scrutiny.